The role of Porphyromonas gingivalis in the pathogenesis of Rheumatoid Arthritis: Review of the literature - Zulma Johanna Moreno Huertas; Johana Jiménez Arbeláez; Sandra Amaya Sánchez; Edison Andrés Cruz Olivo; Jorge Enrique Soto Franco (Universidad Nacional de Colombia, 2018)
Background: Scientific evidence on the relationship between Rheumatoid Arthritis (RA) and Periodontal Disease (PD) has been focused on the presence of the peri- odontopathogen Porphyromonas gingivalis (P.g). Di erent studies have established its relationship with the citrullination process and production of citrullinated antipeptide antibodies. Currently, scienti c evidence on this topic is heterogeneous with new contributions and di erent ndings, but studies in human populations are the ones generating most interest. Objective: To review scientific evidence on clinical studies related to the pathogenesis of Periodontal Disease and Porphyromonas gingivalis in Rheumatoid Arthritis. Methodology: Through a literature search, publications about the de ned topic were identi ed taking into account only of clinical studies. The search period was from 2012 to 2016. The search terms used were: rheumatoid arthritis and Porphyromonas gingivalis. After reviewing titles and abstracts of the papers initially identi ed, literature reviews, case reports, in vitro studies and studies conducted in animals were excluded. Results: After performing the search in three databases (PubMed, Lilacs y Embase), 166 articles were found, 140 articles were rejected and 25 were included given that they described clinical studies on the relationship between RA and P.g. The majority of these studies showed quantitative analysis determining the presence of P.g in patients with RA. In patients with RA and periodontal disease, it is clear the presence of antibodies to P.g in serum, also P.g. DNA, while very little has been reported in synovial uid. New evidence suggests associations with other pathogens and detection in early onset arthritis.